Report on austerity measures and economic and social rights (New York, 2013)
"The present report, submitted pursuant to General Assembly resolution 48/141, considers the impact of austerity measures on economic, social and cultural rights, in particular on the right to work and the right to social security, with a specific focus on women, migrants and older persons. It also lays out the criteria States should apply when considering the adoption of austerity measures."